2021
DOI: 10.1186/s12877-021-02007-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of caregiver burden in aged caregivers of demented older patients

Abstract: Background Dementia in the oldest-old is projected to increase exponentially as is the burden of their caregivers who may experience unique challenges and suffering. Thus, we aim to investigate which factors are associated with older caregivers’ burden in caring demented outpatients in a multicenter cohort. Methods Patients and their caregivers, both aged ≧65 years, in the National Dementia Registry Study in Taiwan (T-NDRS) were included in this st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 50 publications
3
46
2
5
Order By: Relevance
“…Another novelty of our study is the knowledge gained about the care of PSP and CBS patients during initial phases of the disease. Interestingly, we did not find significant correlations between burden of care and patient age, caregiver age or caregiver occupational status, which is in contradiction to other reports in the literature (Tsai et al 2021 ; Schneider et al 1999 ; Iavarone et al 2014 ). The correlations between educational level of the patient and close patient-caregiver relationship (partner or first-degree relative) with CB also need to be verified in future studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Another novelty of our study is the knowledge gained about the care of PSP and CBS patients during initial phases of the disease. Interestingly, we did not find significant correlations between burden of care and patient age, caregiver age or caregiver occupational status, which is in contradiction to other reports in the literature (Tsai et al 2021 ; Schneider et al 1999 ; Iavarone et al 2014 ). The correlations between educational level of the patient and close patient-caregiver relationship (partner or first-degree relative) with CB also need to be verified in future studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Multiple regression analyses demonstrated that deficits in IADL were independently associated with all of the total, PS, and RS scores in ZBI after correcting various patient's conditions. The results agree with the relationship between caregiver burden and IADL reported in previous studies on dementia (21,26) including DLB (3,27). Multiple regression analyses also revealed that the "psychosis" factor was also associated with the total score in ZBI, and that the "affection" factor was independently associated with the total and PS scores in ZBI.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the studies discussing dementia and caregiver burden are cross sectional (Huang et al, 2012 ; Yu et al, 2015 ; Hashimoto et al, 2017 ; Torrisi et al, 2017 ; Branger et al, 2018 ; Kawano et al, 2020 ; Lucijanić et al, 2020 ; Jhang et al, 2021 ; Tsai et al, 2021 ). Most of these articles supported that patient neuropsychiatric symptoms (Huang et al, 2012 ; Hashimoto et al, 2017 ; Torrisi et al, 2017 ; Branger et al, 2018 ; Kawano et al, 2020 ; Tsai et al, 2021 ), poor performance of activities for daily living (ADLs) (Hashimoto et al, 2017 ; Kawano et al, 2020 ; Tsai et al, 2021 ), duration of disease (Kawano et al, 2020 ), female gender, and low education level of the caregiver (Jhang et al, 2021 ) increased the caregiving burden. Worse cognitive function (Yu et al, 2015 ), using daily care services, and the male sex of the patient (Lucijanić et al, 2020 ) were also shown to increase the care burden in some cross-sectional articles.…”
Section: Introductionmentioning
confidence: 99%